Measuring psychological load in sport - Mellalieu, S.; Jones, C.; Wagstaff, C.; Kemp, S.; Cross, M. J. (International Journal of Sports Medicine, 2021)
Monitoring the physical load undertaken by athletes and examining the subsequent relationship with performance and injury and illness risk is common practice in high performance sport. Less attention has been paid to the psychological factors contributing to the overall load experienced and the impact upon health status and performance. This paper discusses considerations for the conceptualization and measurement of psychological load in sport. First, we outline the importance of ensuring conceptual clarity is adopted in the measurement of psychological load. Next, we discuss the challenges to measuring psychological load in a comparable manner to which physical load is currently evaluated, including use of subjective assessment, adoption of specific and global approaches, and development of measurement instrumentation, techniques, and expertise. We then offer recommendations for practitioners when undertaking assessment of psychological load in sport. We conclude with future research directions to advance the study and measurement of the construct, including the interaction between psychological and physical load, the appraisal of the load faced, and personal and social resources available to successfully cope. We also highlight the need to consider groups of athletes (e. g., transitioning athlete, long-term injured) at greater risk from threats to mental and physical health from increased psychological load.